Pengaruh Dosis Adsorben Dan Yang Telah Diaktivasi Waktu Kontak Terhadap Penyisihan Logam Besi (Fe) Dan Warna Air Gambut Menggunakan Adsorben Tanah Lempung Gambut - Dita Yusrita; Syarfi Daud; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Quantitatively, peat water has the potential to be a source of water that can be processed into clean water, but qualitatively the utilization of peat water is still experiencing problems such as high iron (Fe) content and high color. The use of peat water in the long term will have a negative impact on health, so it needs to be processed into clean water. This study aims to study the effect of adsorbent dose and contact time on the efficiency of removal of iron (Fe) and the color of peat water and the adsorption capacity of the adsorption process using physically activated peat clay as an adsorbent. This study varied the adsorbent dose of 4 g/L, 8 g/L and 12 g/L with adsorbent particle size -100 +120 mesh and contact time variations of 120 minutes, 140 minutes and 160 minutes with a stirring speed of 150 rpm. The results showed that the best effect on the removal efficiency was obtained at an adsorbent dose of 12 g/L and a contact time of 160 minutes with a metal removal efficiency of 84.42% and a color removal efficiency of 96.41%. The best effect on the adsorption capacity was the adsorbent dose of 4 g/L and a contact time of 160 minutes with a value of iron (Fe) adsorption capacity of 0.250 mg/g and a color adsorption capacity value of 114.68 mg/g.Keywords: Peat Water, Peat Clay, Adsorption, Physical Activation, Iron Metal (Fe) and Color